Career Development, Job Placement, and Training: Boosting Performance with Job Satisfaction.: Peningkatan Kinerja Karyawan: Pengaruh Pengembangan Karir, Penempatan Jabatan, dan Pelatihan Kerja dengan Kepuasan Kerja sebagai Moderator. - Marfiansyah Ichbal; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative research study aimed to investigate the effect of career development, job placement, and job training on employee performance, with job satisfaction as a moderating variable. A sample of 50 employees from a prominent banking institution participated in this study. The data were collected through a questionnaire, and the analysis was conducted using SPSS statistical software version 25.0. The findings revealed that career development, job placement, and job training have direct positive effects on employee performance. Additionally, job satisfaction was found to have a direct positive impact on employee performance. Furthermore, the interaction between career development and job satisfaction, as well as the interaction between job placement and job satisfaction, significantly influenced employee performance. However, no significant interaction effect was found between job training and job satisfaction. These findings highlight the importance of career development, job placement, and job satisfaction in enhancing employee performance, suggesting practical implications for organizations seeking to optimize their workforce productivity. Highlights: Career development, job placement, and job training have a direct positive influence on employee performance. Job satisfaction plays a crucial role in moderating the relationship between career development and employee performance. The interaction between job placement and job satisfaction significantly affects employee performance. Keywords: Employee performance, Career development, Job placement, Job training, Job satisfaction